UPAYA PENINGKATAN PRSETASI BELAJAR DENGAN MENINGKATAKAN KEMAMPUAN KINERJA GURU MELALUI BIMBINGAN DAN SUPERVISI DI SDN 39 KAMPUNG PANSUR - Marsupiardiono, Marsupiardiono (Jurnal Manajemen Pendidikan, 2018)
Based on observations that researchers have conducted at SDN 39 Kampung Pansur, it was found that the ability of teachers to develop improvement programs for Teacher Performance was still low. The purpose of this study was to describe and obtain information about efforts to improve teacher capacity in developing improvement programs through Guidance and Supervision at SDN 39 Kampung Pansur. This research is a school action research. The research procedure in this study includes planning, action, observation and reflection. This study consisted of two cycles with four meetings. The research subjects consisted of 7 teachers at SDN 39 Kampung Pansur. Research data was collected using observation sheets. Data is analyzed using percentages. The results of the study showed that improving teacher performance could improve students' ability to improve student learning achievement at SDN 39 Kampung Pansur. This is evidenced by an increase in students' ability to develop teacher performance programs from cycle I to cycle II. The average ability of students and teachers in developing teacher performance improvement programs in cycle I was 52.2 with less categories and in cycle II was 82 with good categories